Remote magnetic navigation shows superior long-term outcomes in pediatric atrioventricular (nodal) tachycardia ablation compared to manual radiofrequency and cryoablation. (24th May 2021) - Noten, AME; Kammeraad, JAE; Wijchers, S; Van Beynum, IM; Balinghaus, M; Krasemann, TB; Yap, SC; De Groot, NMS; Szili-Torok, T
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction – Catheter ablation (CA) is a first-choice treatment for tachyarrhythmia in pediatric patients. The currently available CA techniques differ in manner of catheter steering technique and energy sources. There are no large studies comparing long-term outcomes between the available CA techniques in pediatric patients with atrioventricular reentry (also known as accessory pathway mediated) tachycardia (AVRT) or atrioventricular nodal reentry tachycardia (AVNRT) mechanisms. Objective – The aim of this study was to compare procedural parameters and outcomes of remote magnetic navigation-guided radiofrequency (RF) ablation (RMN), manual-guided RF ablation (MAN) and manual-guided cryoablation (CRYO). Methods – This single-center, retrospective study included all first consecutive CA procedures for AVRT or AVNRT mechanisms performed in pediatric patients with no structural heart disease from January 2008 until June 2019. Three study groups were defined by the ablation technique used: RMN, MAN or CRYO. Primary outcome was recurrence of tachyarrhythmia and/or pre-excitation on ECG. Baseline clinical parameters, procedure times and complication rates were also evaluated. Results – In total, we included 223 patients, aged 13.8 ± 2.8 years, with a mean weight of 55.6 ± 14 kilograms. In total, 108 procedures were performed using RMN, 76 using MAN and 39 using Cryo. RMN had the lowest recurrence rates at a mean follow-up of 5.5 ± 2.9 years (AVRT ablation: 4% vs. 16% vs. 55%, P < 0.001; AVNRT ablation: 8% vs. 8% vs. 36%, P = 0.008; for RMN vs. MAN vs. CRYO respectively). In AVRT ablation, procedure and fluor times were comparable between groups. However, in AVNRT ablation, RMN and MAN had significantly lower fluoroscopy times compared to Cryo (10 (IQR 7-14) vs. 9 (IQR 6-26) vs. 15 (IQR 10-22) minutes respectively, P = 0.040). Moreover, procedure times were shortest in MAN and second in RMN ablation (101 (IQR 87-121) vs. 88 (IQR 62-99) vs. 120 (IQR 88-143) minutes respectively, P = 0.018). We observed minor complications in 3 patients (1%), which were comparable between groups and no major complications. Conclusion – In pediatric patients with no structural heart disease who underwent their first AV(N)RT ablation, RMN has the most favorable long-term outcomes, in addition to favorable fluoroscopy and procedure times.